2021
DOI: 10.21577/0100-4042.20170724
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Metabolism of Copalic and Kaurenoic Acids in Rat and Human Liver Microsomes

Abstract: Copalic (CA) and kaurenoic (KA) acids are the main diterpenes found in the oleoresin extracted from the copaiba tree (Copaifera sp). This study aimed to characterize the metabolism of CA and KA in rat and human liver microsomes using liquid chromatography with tandem mass spectrometry (LC-MS/MS). The in vitro assays showed deviations from the Michaelian kinetics in the metabolism of CA and KA. Putative metabolites of CA and KA were characterized by LC-MS/MS using electrospray ionization (ESI) with time of fli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…On the other hand, biomimetic models are simple, with fewer interferences in the reaction medium, allowing the detection of minority products. This model has been applied to understand the phase I metabolism of several natural products, such as lapachol [12], piplartine [24][25], grandisin [26][27][28], monensin [29], and kaurenoic acid [9,30], in which some products were also observed using microsomal models or in vivo models. In this work, it was demonstrated that the biomimetic oxidation of licarin A by Jacobsenʼs catalyst was able to reproduce the oxidation system with RLM and HLM.…”
Section: Original Papersmentioning
confidence: 99%
“…On the other hand, biomimetic models are simple, with fewer interferences in the reaction medium, allowing the detection of minority products. This model has been applied to understand the phase I metabolism of several natural products, such as lapachol [12], piplartine [24][25], grandisin [26][27][28], monensin [29], and kaurenoic acid [9,30], in which some products were also observed using microsomal models or in vivo models. In this work, it was demonstrated that the biomimetic oxidation of licarin A by Jacobsenʼs catalyst was able to reproduce the oxidation system with RLM and HLM.…”
Section: Original Papersmentioning
confidence: 99%
“…Humans have used plants to treat several diseases for centuries, but only recently traditional medicine has encouraged novel research with natural products, either bioactive compounds or complex mixtures such as extracts, fixed oils, essential oils, and oil-resin (Petrovska, 2012). Some plant species such as the genus Copaifera have different classes of secondary metabolites that may have potential pharmacological applications (Maciel et al, OPEN ACCESS EDITED BY Mohammad S. Mubarak, The University of Jordan, Jordan 2002; Palombo, 2011;Mauro et al, 2021). The Copaiba tree (Figure 1) is a member of the Fabaceae family, the Caesalpinioideae subfamily, and the Copaifera genus.…”
Section: Introductionmentioning
confidence: 99%